Chromosome Segregation-1-like Gene Participates in Ferroptosis in Human Ovarian Granulosa Cells via Nucleocytoplasmic Transport - Luanqian Hu; Tongtong Hong; Yuheng He; Huiyuan Wang; Jinxiang Cao; Danhua Pu; Li Gao; Chao Gao; Yugui Cui; Jie Wu; Rongrong Tan (MDPI AG, 2024)
Premature ovarian insufficiency (POI) is defined as the depletion of ovarian function before the age of 40 years. The global prevalence of POI is 3.5%. To date, genetic factors account for 23.5% of the etiology of POI. Herein, a previously uncharacterized pathogenic homozygous variant of the chromosome segregation-1-like gene (CSE1L) was identified in POI patients via targeted panel sequencing. It is reported that dysregulated iron metabolism is involved in many reproductive endocrine disorders; however, its precise role in POI remains obscure. In this study, we identified CSE1L as a potential candidate gene that plays an important role in maintaining iron homeostasis. Deficiency of CSE1L led to ferroptosis in human granulosa cells, which was confirmed by transmission electron microscopy. Mechanistically, coimmunoprecipitation identified the direct interaction between CSE1L and FoxO1. Inhibition of CSE1L led to the excessive accumulation of FoxO1 in the nucleus via nucleocytoplasmic transport. Then, FoxO1 bound to the promoter region of NCOA4 and promoted its transcription, which was verified by a chromatin immunoprecipitation assay. Moreover, inhibition of CSE1L in cumulus cell monolayer could impede oocyte maturation, which might be associated with oxidative stress. Consequently, our study first revealed that CSE1L participated in ferroptosis in human ovarian granulosa cells via nucleocytoplasmic transportation, which might be helpful in revealing the molecular mechanism of CSE1L in the development of POI. Importantly, these findings might provide new insights into the application of ferroptosis inhibitors in the treatment of POI.